Existence of value functions of differential games with incomplete information in partially order spaces. (4th May 2023) - Shao, Menghao; Hong, Shihuang; Cao, Xiaoyu; Luo, Xinggang
Abstract : In this paper, we consider a two-person zero-sum differential game with incomplete information on the initial state, namely, the first player has a private information while the second player knows only a probability distribution on the initial state, and obtain the existence of its value functions. The main novelty lies in the method for which we apply a generalized weak contraction for dynamic systems and terminal cost functions instead of the Lipschitz contractive condition on a partially ordered metric space.